Charge behavior modulation by titanium-carbide quantum dots and nanosheets for efficient perovskite solar cells. (December 2020) - Ge, J.; Li, W.; He, X.; Chen, H.; Fang, W.; Du, X.; Li, Y.; Zhao, L.
Abstract: Efficient charge transfer with suppressed charge recombination is crucial for perovskite solar cells (PSCs) with high photovoltaic performance. Herein, Ti3 C2 quantum dots (QDs) are introduced into the perovskite layer, and Ti3 C2 nanosheets are inserted into the TiO2 electron transport layer (ETL). The results confirm that the incorporation of Ti3 C2 QDs can effectively reduce the defect state concentration of perovskite films, and the Ti3 C2 nanosheets can improve the electron mobility of the ETL. By taking advantages of zero- and two-dimensional Ti3 C2, the performance of PSC achieves an enhancement of photoelectric conversion efficiency from 12.0% to 17.1%, along with reduced hysteresis effect of the device. This article explores a promising strategy to exploit MXenes in the application of PSCs. Graphical abstract: Schematic diagram of the device. Image 1 Highlights: Ti3 C2 QDs are successfully synthesized and incorporated in the perovskite layer. Ti3 C2 QDs can assist to improve the crystallinity of the perovskite. Ti3 C2 QDs can efficiently passivate defects, thus reducing carrier recombination. Ti3 C2 nanosheets are added into TiO2 to promote charge extraction. The modified perovskite solar cells exhibit significantly enhanced PCE.